Análise e aplicabilidade da manutenção para melhoria contínua em uma indústria do setor automobilístico - Galhardo, Leonardo Matias (2022)
Two are the main types of maintenance used in the sector today, the main ones being preventive and corrective. Considering this in a continuous production process, it ends up not being the most effective way to maintain a high reliability of the process. There is a need for a brief study of information, seeking data that are valid and that helps the search for a process of continuous improvement. By making this data available, you can point out errors and give a north to future maintenance plans. The work began by performing an analysis of the tool times still by corrective maintenance, cycle time, preventive maintenance time. Since this value is very high in relation to the availability and cost of labor, the work seeks to evaluate a way to balance the times in a way that can gain in availability and confidence in the production process. With this information it was possible to identify and mitigate process failures, having significant gain in production. The need for a more modern system of treatment and presentation of indicators was of great importance for the development of activities and improvements. For this, a system of data collection, information processing, modern presentation models and the analysis of improvements that were made were created was created. Where the main problems could be seen and dealt with in a timely and optimized way.